EFEKTIFITAS MEDIA FILM DAN ULAR TANGGA TERHADAP PENGETAHUAN DAN SIKAP ANAK SD TENTANG PENYAKIT KECACINGAN DESA TANOH MIRAH KECAMATAN PEUSANGAN KABUPATEN BIREUEN - Syarifah Hanum (Universitas Islam Negeri Sumatera Utara, Medan, 2021)
AbstractWorms is still a problem that easily found in children in Indonesia. Worms will cause many problems to children, such as intelligence, other infections and nutritional status. The purpose of this study was to determine the effect of health promotion using snakes and ladders and film media in increasing awareness and attitudes of elementary school children in Tanoh Mirah Peusangan, Bireuen Regency. This study used a quasi-experimental design. The research sample was 40 elementary school children and divided them into two groups, namely 20 children with snake and ladder media intervention and 20 children with film media intervention. Wilcoxon analysis used to see the increase in knowledge and attitudes before and after media intervention.Results: The results of the Wilcoxon test showed that the media of film and the media of snakes and ladders succeeded in increasing the scores of elementary students' knowledge and attitudes regarding the prevention of worm disease. Health promotion using snake and ladder media was proven to be more effective in increasing the scores of elementary students' knowledge and attitudes about preventing worm disease compared to using film media.Snakes and ladders and films media have been shown to increase knowledge and attitudes towards preventing worm disease. The Bireuen District Health Office and the Bireuen District Education Office expected to carry out various health promotion activities to prevent worm disease by using the snake and ladder game; it has been proven effective in increasing the knowledge and attitudes of elementary school students.